The face of the unknown - Bennett, Christopher L (Star trek, the original series., 2017)
When their investigation of violent raids leads them to the home of the First Federation, Captain Kirk and the crew of the U.S.S. Enterprise try to convince the group's leaders to overcome their fears and stave off a catastrophe.